The Effect of Non-Physical Work Environment and Organizational Commitment on Employee Performance with Job Satisfaction as Intervening Variables - Rina Mutiara; Novi Fitria Hermiati (STKIP Yapis Dompu, 2023)
A private or government organization really needs quality human resources and has maximum performance to drive the wheels of the organization. The problem that occurs is the decline in the performance of Human Resources (HR) which causes these government agencies to be unable to provide the best service for the community. Then he still feels uncomfortable and the level of communication that is still low is very influential in work efficiency in an agency, which has an impact on employee absenteeism, decreased motivation and performance and lost productivity. The method used in this research is Structural Equation Modeling (SEM) analysis using Lisrel software version 8.80. Saturated sample technique or total sampling is the method used in this study and the number of research samples is 82 employees. The results of this study prove that 1) The non-physical work environment and organizational commitment both substantially and simultaneously have an influence on job satisfaction. 2) the non-physical work environment has no effect on performance. 3) Organizational commitment significantly influences performance 4) Job satisfaction influences performance 5) Job satisfaction can be said to be an intervening variable because the value of the indirect effect of each variable is greater than the direct effect.